Temperature Compensation of Fiber Bragg Grating Sensors in Smart Strand - Jeon, Se Jin; Park, Sung Yong; Kim, Sung Tae (Sensors, 2022)
Compared to other types of sensors, fiber optic sensors have improved accuracy and durability. Recently, the Smart Strand was developed to maximize the advantages of fiber optic sensors for measuring the cable forces in prestressed concrete structures or cable-supported bridges. The Smart Strand has fiber Bragg gratings (FBGs) embedded in a core wire of the seven-wire strand. Similar to other sensors, the strain measured at an FBG is affected by temperature; therefore, the temperature effect that is not related to the mechanical strain should be compensated for or corrected in the long-term measurement subjected to temperature variation. However, a temperature compensation procedure for the FBG has yet to be established, and relevant studies have used different formulas for the compensation. Moreover, when the FBG sensors are packaged with a certain material—such as fiber reinforced polymer—for protection, it is important to consider the interaction between the FBG, packaging material, and host material during thermal behavior. Therefore, this study proposed a reasonable procedure for temperature compensation for the FBG sensors embedded in packaging material and host material. In particular, the thermal sensitivity of the Smart Strand was intensively investigated. The proposed theoretical formulas were validated through comparison with data obtained from various specimens in a temperature-controlled chamber. Finally, the procedure was applied to correct the data measured using the Smart Strands in a 20-m-long full-scale specimen for about a year, thus resulting in a realistic trend of the long-term prestressing force.
Keywords: Cable forces; Fiber Bragg Grating Sensors; Fibre-optic sensor; Host materials; Prestressing forces; Prestressing tendon; Strand; Temperature compensation; Temperature correction; Thermal sensitivity; Fiber Optic Technology; Mechanical Phenomena; Optical Fibers; Temperature; FBG; fiber Bragg grating; fiber optic sensor; prestressed concrete; prestressing force; prestressing tendon; strand; temperature compensation; temperature correction; thermal sensitivity